2017
DOI: 10.1051/0004-6361/201629608
|View full text |Cite
|
Sign up to set email alerts
|

Confronting semi-analytic galaxy models with galaxy-matter correlations observed by CFHTLenS

Abstract: Testing predictions of semi-analytic models of galaxy evolution against observations help to understand the complex processes that shape galaxies. We compare predictions from the Garching and Durham models implemented on the Millennium Run with observations of galaxy-galaxy lensing (GGL) and galaxy-galaxy-galaxy lensing (G3L) for various galaxy samples with stellar masses in the range 0.5 ≤ M * /10 10 M ⊙ < 32 and photometric redshift range 0.2 ≤ z < 0.6 in the Canada-France-Hawaii Telescope Lensing Survey (CF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 49 publications
5
26
0
Order By: Relevance
“…To test our reconstruction technique, we employ a fiducial survey with a sky coverage of ∼ 1000 deg 2 , and a photometry and a survey depth as in CFHTLenS. To construct realistic samples of lenses and sources, we have prepared mock catalogues that are consistent with those used in SES13 and Saghiha et al (2017). Despite some variations in survey depth and area, these survey parameters are similar to the ongoing Kilo-Degree Survey (KiDS), Dark Energy Survey (DES), or the survey with the Hyper Suprime-Cam (Kuijken et al 2015;Becker et al 2016;Aihara et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To test our reconstruction technique, we employ a fiducial survey with a sky coverage of ∼ 1000 deg 2 , and a photometry and a survey depth as in CFHTLenS. To construct realistic samples of lenses and sources, we have prepared mock catalogues that are consistent with those used in SES13 and Saghiha et al (2017). Despite some variations in survey depth and area, these survey parameters are similar to the ongoing Kilo-Degree Survey (KiDS), Dark Energy Survey (DES), or the survey with the Hyper Suprime-Cam (Kuijken et al 2015;Becker et al 2016;Aihara et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These SAMs are the H15 mocks that are also used in Saghiha et al (2017). The Millennium Simulation (MS) is a N-body simulation of the CDM density field inside a comoving cubic volume of 500 h −1 Mpc side length, and it has a spatial resolution of 5 h −1 kpc sampled by 10 10 mass particles.…”
Section: Samples Of Lens Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of various SAMs that have been implemented on the MR (see e.g. Guo et al 2011;Bower et al 2006), but as Saghiha et al (2017) have shown, this model agrees particularly well with measurements of GGL and G3L in CFHTLenS. To simulate the selection function of observations, we apply a redshift and flux limit on our lens samples.…”
Section: Simulated Data Based On the Mrmentioning
confidence: 74%
“…As discussed in Saghiha et al (2012) and recently shown by Saghiha et al (2017, hereafter S17) galaxy-galaxy-galaxy lensing can test SAMs by comparing model predictions for the average matter density around galaxy pairs to measurements. The analysis in S17 is based on the CFHTLenS 1 measurements in Simon et al (2013), S13 herafter, and uses lens galaxies with stellar masses between ∼ 10 9 − 10 11 M and redshifts below z 0.6.…”
Section: Introductionmentioning
confidence: 96%